2013
DOI: 10.1007/s11427-013-4479-z
|View full text |Cite
|
Sign up to set email alerts
|

Different quasispecies with great mutations hide in the same subgroup J field strain of avian leukosis virus

Abstract: Blood samples were collected from a local strain of chickens associated with serious tumor cases in Shandong Province. The samples were inoculated into chicken embryo fibroblast and DF-1 cells for virus isolation and identification, respectively. The inoculated cells were screened for three common chicken tumor viruses. Nine strains of avian leukosis virus subgroup J (ALV-J) were identified, and were designated LY1201-LY1209. The env gene from the LY1201 strain was amplified and cloned. All nine resultant env … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In these reports, only one clone of any ALV-J isolate representing an infected bird, flock, or farm in a given period was sequenced; thus, the genomic diversity of ALV-J strains circulating in the same bird or flock was not considered. However, our laboratory detected such diversity in the gp85 gene of an ALV-J field isolate when more clones were selected for sequence comparisons [12]. …”
Section: Discussionmentioning
confidence: 99%
“…In these reports, only one clone of any ALV-J isolate representing an infected bird, flock, or farm in a given period was sequenced; thus, the genomic diversity of ALV-J strains circulating in the same bird or flock was not considered. However, our laboratory detected such diversity in the gp85 gene of an ALV-J field isolate when more clones were selected for sequence comparisons [12]. …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the ALV-J infection has been very common among chicken flocks during the last 20 years in China, such as in white meat-type chickens before 2006 (Du et al, 2000;Cui et al, 2003;Zhang et al, 2004) and in layers in 2002 to 2013 (Xu et al, 2004;Guo et al, 2009;Gao et al, 2012;Cai et al, 2013). This virus continues to spread in different Chinese local breeds (Cheng et al, 2005;Cui et al, 2009;Mao et al, 2013) although eradication programmes have been initiated in some breeder farms. Previous studies have indicated that the extent of immunosuppression and pathogenicity were different among chicks with multiple as well as single viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…All of the viruses isolated from diseased chickens with tumors belonged to ALV-J. 8 , 9 , 10 In contrast, ALV-A, ALV-C, and viruses belonging to the new subgroup K were isolated from clinically healthy chickens. Therefore, the pathogenicity of ALV-J was relatively high among the indigenous chicken breeds.…”
mentioning
confidence: 99%